Abnormal serum growth hormone response to exercise in juvenile diabetics - Hansen, Aage Prange (The Journal of Clinical Investigation, 1970)
Groups of male nonobese juvenile diabetics with recent onset, short term (1-8 yr), and long-term (12-30 yr) diabetes as well as comparable nondiabetic controls were studied during exercise experiments. The chosen exercise load, 450 kg/min for 20 min never induced changes in serum growth hormone in our nondiabetic control subjects. The principal results of the study were as follows: (a) an immediate high rise in serum growth hormone followed the commencement of exercise in all diabetics. The increase and pattern of serum growth hormone was not related to the duration of the diabetes. (b) The abnormal growth hormone response to exercise in diabetics was observed when the patients were in poor control as well as when they were in clinically excellent control (fasting blood glucose level between 100 and 140 mg/100 ml). (c) However, the abnormal serum growth hormone response was significantly diminished when exceedingly strict control was achieved (fasting blood glucose level between 60 and 100 mg/100 ml). In two of these experiments an entirely normal growth hormone pattern was obtained. (d) The change in serum growth hormone pattern during regulation was totally unrelated to the changes in serum free fatty acid patterns. A normal free fatty acid level and exercise pattern was obtained much earlier during the improved control. (e) Fasting serum growth hormone levels were also significantly raised in the juvenile diabetics irrespective of the diabetes duration. (f) Fasting serum growth hormone levels were also significantly decreased during regulation. Furthermore, a significant correlation between blood glucose and fasting serum growth hormone concentration was established. (g) In the juvenile diabetics a significant increase in serum insulin was observed at the point of time when exercise was concluded.